2022
DOI: 10.11591/ijeecs.v27.i1.pp71-78
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of electro-hydraulic telescopic elevator system controlled by programmable logic controller

Abstract: Traditional hydraulic <span>cylinders are widely used in industry as load lifting tools. There is difficulty in employing these cylinders in narrow installation space like building elevators as well as they require a long working stroke, so solving this problem requires using the telescopic hydraulic cylinder instead. This cylinder is a unique hydraulic cylinder design that uses a sequence of decreasing diameters to create a long operating stroke in a compact-retracted form. In this work, the Auto Statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Hady et al [14] employed the 4-stages telescopic cylinder in building a PLC-based elevator system for lifting purposes as shown in Figure 7. The study findings, which included typical curves for cylinder position and speed, demonstrated the simulated model's correctness and believability.…”
Section: Comprehensive Review Of Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Hady et al [14] employed the 4-stages telescopic cylinder in building a PLC-based elevator system for lifting purposes as shown in Figure 7. The study findings, which included typical curves for cylinder position and speed, demonstrated the simulated model's correctness and believability.…”
Section: Comprehensive Review Of Literaturementioning
confidence: 99%
“…The theoretical analysis of the telescopic hydraulic cylinder is represented by all of the studies in Table 1, while the studies in Table 2 are concerned with designing and implementing an effective and smooth control of the motion of the telescopic hydraulic cylinder. The elevator system in the studies [13,14] differs from the all previously mentioned cylinders or lifting systems in that it is constructed using a telescopic hydraulic cylinder as a driving mechanism.…”
Section: Table 1 Software Analysismentioning
confidence: 99%
See 3 more Smart Citations